2018
DOI: 10.3892/ijmm.2018.3916
|View full text |Cite
|
Sign up to set email alerts
|

Lithocarpus�polystachyus Rehd. leaves aqueous extract protects against hydrogen peroxide‑induced SH-SY5Y cells injury through activation of Sirt3 signaling pathway

Abstract: Lithocarpus polystachyus Rehd. (sweet tea; ST) leaves is a type of chinese folkloric medicine from southern china. The purpose of the present study was to explore the neuroprotective effect of ST, and to explore its underlying mechanisms in hydrogen peroxide (H 2 O 2)-induced neuronal cell injury in cultured human neuroblastoma. H 2 O 2 was used as oxidant inducer and human SH-SY5Y neuroblastoma cells were treated with various concentrations of ST. cell viability and cell death were detected using MTT and LdH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In 2017, sweet tea was listed as a new food material by the National Health and Family Planning Commission of China. It contains plentiful polysaccharides, flavonoids, and polyphenolic ingredients, which have extensive biological properties, such as anti-diabetic, anti-hypertensive, neuroprotective, hepatoprotective, and anti-aging effects [3][4][5]. As some of the main bioactive components in sweet tea, sweet tea polysaccharides (STPs), however, have not been intensively investigated in respect of their structural and biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, sweet tea was listed as a new food material by the National Health and Family Planning Commission of China. It contains plentiful polysaccharides, flavonoids, and polyphenolic ingredients, which have extensive biological properties, such as anti-diabetic, anti-hypertensive, neuroprotective, hepatoprotective, and anti-aging effects [3][4][5]. As some of the main bioactive components in sweet tea, sweet tea polysaccharides (STPs), however, have not been intensively investigated in respect of their structural and biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are the main bioactive components of sweet tea and also major contributors to its sweetness [ 3 ]. Sweet tea and its bioactive components have been found to have antioxidant, antimicrobial, anti-inflammatory, antidiabetic, anticancer and cardiovascular protective activities [ 4 , 5 , 6 , 7 , 8 , 9 ]. The effective extraction of bioactive components in sweet tea is helpful for its exploitation and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The human neuroblastoma (SH-SY5Y) cell death model mediated by H 2 O 2 is widely used to study neuronal cell death caused by oxidative stress and neuroprotective effects of natural products [ 36 , 37 ]. The present study results indicated the H 2 O 2 -induced SH-SY5Y cell death was significantly reduced by pretreatment with FMA.…”
Section: Discussionmentioning
confidence: 99%